(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the methodology of creating works of art using digital technologies. It analyzes the integration of digital tools in the creative process of contemporary art, highlights key methods and strategies employed by artists, and evaluates their impact on aesthetic and conceptual dimensions of artwork. The study also addresses how digital art methodologies reshape educational practices in art institutions, redefine authorship, and contribute to the democratization of art production and distribution. By examining current trends and innovative approaches, the article emphasizes the significance of digital technologies in shaping the future of art.